Assessment of Yellow and White Fleshed Cassava Tuberous Root Cultivars Reveals Different Responses to Post-harvest Physiological Deterioration - Rahmawati, Rika Sri; Fathoni, Ahmad; Sukma, Dewi; Ardie, Sintho Wahyuning; Sudarsono, Sudarsono (Journal of Tropical Crop Science, 2024)
Identification of post-harvest physiological deterioration (PPD) tolerance in cassava is crucial, as PPD significantly hampers the cassava tuberous root industry by shortening storage periods post-harvest and diminishing product quality. Characteristics linked to PPD tolerance encompass high carotenoid levels and low dry matter content (DMC). This study aimed to evaluate the PPD responses of six yellow fleshed and ten white-fleshed cassava tuberous roots and determine the source of PPD tolerance. PPD and DMC assessments were conducted using standard methods at three storage periods: 2, 5, and 10 days after harvest (DAH). The k-means clustering analysis revealed six clusters, each corresponding to distinct PPD symptom patterns and tolerance statuses. Cluster 1, comprising three yellow-fleshed and three white-fleshed cassava cultivars, demonstrated PPD tolerance with minimal symptoms up to 5 DAH. Clusters 2 and 3 exhibited a moderate PPD response with elevated symptoms at 5 DAH, comprising three yellow-fleshed and three white-fleshed cassava cultivars. Clusters 4 to 6 displayed a sensitive response to PPD, showcasing a significant increase in symptoms at 5 and 10 DAH, with four white-fleshed cassava cultivars identified within this cluster. These findings underscored the presence of PPD tolerance in both yellow-fleshed and white-fleshed cassava tuberous roots. The correlation between PPD and DMC was significant only at 2 DAH, displaying a moderate positive correlation. Consequently, this study identified three cultivars, “Carvita-25”, “Manggu”, and ““Ubi Kuning””, with high DMC and low PPD incidence at 5 DAH, suggesting their suitability for further breeding programs.